2022
DOI: 10.1038/s41467-022-31872-6
|View full text |Cite
|
Sign up to set email alerts
|

Extreme purifying selection against point mutations in the human genome

Abstract: Large-scale genome sequencing has enabled the measurement of strong purifying selection in protein-coding genes. Here we describe a new method, called ExtRaINSIGHT, for measuring such selection in noncoding as well as coding regions of the human genome. ExtRaINSIGHT estimates the prevalence of “ultraselection” by the fractional depletion of rare single-nucleotide variants, after controlling for variation in mutation rates. Applying ExtRaINSIGHT to 71,702 whole genome sequences from gnomAD v3, we find abundant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 63 publications
4
16
0
Order By: Relevance
“…We show a strong bias for GC4 content at constrained sites, which may help 'flag' transcripts as native 22 , and that single-exon genes and first exons of multi-exon genes have higher GC4 content across mammals, a pattern previously shown in humans 26 . We also show strong evidence for high constraint at 4d sites that occur at exon-intron boundaries, essential for ensuring the production of accurate transcripts 26,[46][47][48] . Whilst constraint on 4d sites at exon boundaries is generally high, it explains <3% of the overall 4d constraint we observe.…”
Section: Discussionmentioning
confidence: 64%
“…We show a strong bias for GC4 content at constrained sites, which may help 'flag' transcripts as native 22 , and that single-exon genes and first exons of multi-exon genes have higher GC4 content across mammals, a pattern previously shown in humans 26 . We also show strong evidence for high constraint at 4d sites that occur at exon-intron boundaries, essential for ensuring the production of accurate transcripts 26,[46][47][48] . Whilst constraint on 4d sites at exon boundaries is generally high, it explains <3% of the overall 4d constraint we observe.…”
Section: Discussionmentioning
confidence: 64%
“…However, we note that a major limitation of our study is that we are unable to finely estimate selection and dominance parameters for strongly deleterious mutations, which as defined here encompass a wide range of |s| from 0.01 to 1. This limitation is due to SFS-based methods being underpowered for estimating the strongly deleterious tail of the DFE [44], due to the fact that such mutations tend not to be segregating in genetic variation datasets [48][49][50]. Thus, an important area for future work is to further refine selection and dominance parameters for strongly deleterious mutations and determine whether dominance parameters may differ between strongly deleterious mutations (|s| on the order of ~0.01) and lethal mutations (|s|=1).…”
Section: Discussionmentioning
confidence: 99%
“…This apparently strong purifying selection has been proven difficult to reconcile with recent findings demonstrating remarkable resilience of UCNEs to variation (Snetkova, Ypsilanti, et al, 2021). Moreover, it has been suggested that weaker but uniform levels of purifying selection across hundreds of bases and different species could bring together these otherwise contradictory observations and explain why rare variants are not significantly depleted within UCNEs (Dukler et al, 2022). Our primary search space for variants with potential functional effects comprised 178 ultrarare variants located within 84 putatively active UCNEs associated with 29 genes.…”
Section: Discussionmentioning
confidence: 99%